Estratégias de produção e organização de informações na WWW: uma análise de sites turísticos - Carlos Frederico de Brito D'andrea (2005)
The present dissertation analyses, under different viewpoints, websites about historical cities and communities recognized as world heritage sites" by Unesco. The justification for carrying out this study is the importance of the so called local contents in enabling regions or communities to play active roles in the multiple information and opinionuniverse that the internet is. A new method for analyzing websites is proposed, which tries to identify and debate the strategies adopted in their elaboration and updating, considering mainly: 1) the production /gathering and organization of the available information; 2) the characteristics of the electronic document, regarding the specific aspects of touristic information and of the WWW hypertextual environment; 3) the nature of the information unit responsible for the website. Four websites were the samples utilized during the research: two which contemplated the Historical Center of Olinda, in the state of Pernambuco (Olinda Virtual - http://www.olindavirtual.net/; and the Olinda City hall website -http://www.olinda.pe.gov.br) and two more which contemplated the Historical Center of Diamantina City, in the state of Minas Gerais (DiamantinaNet - http://www.diamantinanet.com.br - and Idas Brasil -http://www.idasbrasil.com.br/idasbrasil/cidades/Diamantina/port/apresent.asp). The data collected allow us to understand the operation of the selected websites and to debate their strengths and weaknesses. Among other observations, the following points were identified: the difficulty in balancing a great volume of information with its organization, the limited use of the WWW hypertextual potential and the absence of some information of touristic interest. In the conclusions of the study, we were able to, first and foremost, evaluate the proposed method of analysis, identifying its merits, such as the possibility of an ample understanding of a websites characteristics, and its limitations, such as the inadequacy of some of the concepts when withdrawn from traditional information units and placed in the digital context. At the end of the research, it was also possible to point out suggestions for futuredevelopments in the area, like the creation of collaborating nets which allow each website to explore its specificity to the fullest without loosing institutional autonomy.